2009
DOI: 10.5194/nhess-9-1713-2009
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of lightning data provided by ZEUS and LINET networks over Western Europe

Abstract: Abstract. In the framework of this paper, one-year of lightning data from the experimental network ZEUS operated by the National Observatory of Athens is compared to collocated data provided by the LINET detection network. The area of comparison is limited to a part of Central-Western Europe, where LINET data exhibits the highest data quality, permitting thus to be used as the validation dataset. The location error of ZEUS was calculated to be ∼6.8 km, while the detection efficiency was ∼25%, with a characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 10 publications
(14 reference statements)
2
64
0
4
Order By: Relevance
“…6a-c). This example, among others, confirms the capability of sferic-detecting networks to locate some IC components, as Lagouvardos et al (2009) already reported with ZEUS and LINET. The HyMeX SOP1 data offer a unique opportunity to not only study the CG and IC detection efficiencies as well as location accuracy, but also to investigate the discharge properties with a signal strong and well pronounced enough to be detected and located by long range VLF detection systems.…”
Section: Examples Of Unusual Lightning Flashessupporting
confidence: 67%
See 1 more Smart Citation
“…6a-c). This example, among others, confirms the capability of sferic-detecting networks to locate some IC components, as Lagouvardos et al (2009) already reported with ZEUS and LINET. The HyMeX SOP1 data offer a unique opportunity to not only study the CG and IC detection efficiencies as well as location accuracy, but also to investigate the discharge properties with a signal strong and well pronounced enough to be detected and located by long range VLF detection systems.…”
Section: Examples Of Unusual Lightning Flashessupporting
confidence: 67%
“…Further details on the ZEUS network are given in Kotroni and Lagouvardos (2008). Lagouvardos et al (2009) have compared the ZEUS system with the LINET system over a major area of central-western Europe, where the latter system presents its major efficiency and accuracy, and found that the location error of ZEUS was 6.8 km and the detection efficiency 25 %. These numbers are also applicable for the SOP1 domain.…”
Section: Zeusmentioning
confidence: 99%
“…Not all the rain gauges were used for every rainy event, since precipitation measurements were not always readily available due to gaps in the data or rain gauge malfunctioning. Lightning data retrieved from the ZEUS system were provided by the National Observatory of Athens (NOA) in Greece (an assessment of the performance of the ZEUS system has been presented by Morales et al, 2007, and, more recently, by Lagouvardos, 2008, andLagouvardos et al, 2009).…”
Section: Datamentioning
confidence: 99%
“…One of these land stations is in operation at Larnaka Meteorological Office, located on the southeast coast of Cyprus, since 2002. ZEUS has a very good coverage of the area of the Eastern Mediterranean; the system is administrated and the data are Correspondence to: S. Michaelides (silas@ucy.ac.cy) archived by the National Observatory of Athens (NOA), in Greece (see Lagouvardos et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation